2011
DOI: 10.1016/j.ijsolstr.2011.01.035
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic analysis of fretting-wear in friction contact interfaces

Abstract: a b s t r a c tA numerical treatment of fretting-wear under vibratory loading is proposed. The method is based on the Dynamic Lagrangian Frequency Time method. It models unilateral contact by using Coulomb's friction law. The basic idea is to separate time into two scales, a slow scale for tribological phenomena and a fast scale for dynamics. For a given number of vibration periods, a steady state is assumed and the variables are decomposed into Fourier series. An Alternating Frequency Time procedure is perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…This nonlinear system is solved by means of the alternating frequency time procedure (AFT) [9,16] depicted in Fig. 2.…”
Section: Nonlinear Dynamic Analysismentioning
confidence: 99%
“…This nonlinear system is solved by means of the alternating frequency time procedure (AFT) [9,16] depicted in Fig. 2.…”
Section: Nonlinear Dynamic Analysismentioning
confidence: 99%
“…A study of fretting-wear in dovetail attachments during blade-disk vibration was described in a previous paper [5,6] and it was shown that steady state can occur. Therefore it would be useful to have a method capable of calculating the steady state caused by fretting-wear under dynamical loading directly.…”
Section: Fretting-wear With Pseudo-timementioning
confidence: 99%
“…For CFD applications, several authors [1,3,4] propose transforming the non-linear algebraic system into a first order differential system and integrating it to obtain the steady state and thus the solution of the non-linear system. The second section sets out the theory of this method and different schemes are tested by using numerical examples.In previous papers [5][6][7] we have shown that steady state in fretting-wear can occur during vibration. To identify steady state we proposed an integration scheme involving the calculation of transient kinetics.…”
mentioning
confidence: 93%
“…This allows a much finer discretisation of the contact area while keeping computational cost low. Salles et al [8,9] also used a multi-scale approach but they proposed a numerical treatment of fretting-wear under vibratory loading. In their approach, two separate time scales are used: a slow scale for tribological phenomena and a fast scale for dynamics.…”
Section: Introductionmentioning
confidence: 99%